Rezolvati ecuatiile :
![2 \frac{3}{8} ( \frac{1}{3} -3x)+ \frac{5}{8 } ( \frac{1}{3} - 3x) =1 2 \frac{3}{8} ( \frac{1}{3} -3x)+ \frac{5}{8 } ( \frac{1}{3} - 3x) =1](https://tex.z-dn.net/?f=2+%5Cfrac%7B3%7D%7B8%7D+%28+%5Cfrac%7B1%7D%7B3%7D+-3x%29%2B++%5Cfrac%7B5%7D%7B8+%7D+%28+%5Cfrac%7B1%7D%7B3%7D+-+3x%29+%3D1)
Răspunsuri la întrebare
Răspuns de
1
Răspuns de
1
[tex]2 \frac{3}{8}( \frac{1}{3}-3x)+ \frac{5}{8}( \frac{1}{3}-}3x)=1 \\ \\
( \frac{1}{3}-^{3)}3x)( \frac{19}{8}+ \frac{5}{8}) = 1 \\ \\
(\frac{1}{3}- \frac{9x}{3})* \frac{24}{8}=1 \\ \\
\frac{1-9x}{3}*3=1 \\ \\
1-9x=1 \\ \\
9x=0 \Longrightarrow \boxed{x=0}[/tex]
http://brainly.ro/tema/536699 ?
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
10 ani în urmă
Fizică,
10 ani în urmă
Matematică,
10 ani în urmă
Istorie,
10 ani în urmă
ajuta-ma te rog si aici